Implementation of Policy for the Development of Village Owned Business Entities in Klaten Regency, Central Java Province - Joni Agung Priyanto; Khasan Effendy; Ika Sartika; Nuryanto Nuryanto (Budapest International Research and Critics University, 2022)
The phenomenon that is the object of research is the implementation of BUMDes development policies in Klaten Regency. The research objectives are: to analyze the implementation of BUMDes development policies in Klaten Regency; and, compiling models. This study uses a qualitative method. The 14 research informants were determined by purposive sampling and accidental sampling technique. Secondary data collection using literature study; primary data collection using interview and observation techniques discussion of research results uses descriptive analysis which was developed with observer triangulation analysis. The results of the study show that the implementation of BUMDes development policies in Klaten Regency has not been optimal. Due to the lack of communication and connectivity with the BUMDes resource development system and business network which is institutionalized in stages and widely, the limited commitment, competence, and performance are not yet result-oriented. The model composed of the results of the analysis is the JAP BUMDes Development Implementation Model (Implementation Network and Business Expansion Network; Accountability and Mindset Change). Practical advice is to expand the BUMDes Forum, so as to form implementation networks and business development networks, increase accountability and change the mindset of policy makers and policy actors, through coaching, socialization of learning in a directed and integrated manner and continuous supervision. Theoretical suggestions to the academic community to be willing to develop a structured JAP BUMDes Development Implementation Model.